The Impact of The Usefulness E-Government of Disdukcapil Bekasi City Through Digital Service Innovation - Niswa Adlina Labiba; Shavira Putri Damayanti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This research found problems faced by conventional services at the Bekasi Population and Civil Registration Office in the form of limited blank forms, minimal waiting rooms, limited computer equipment, complicated procedures, brokers, and discrimination. Through digital service transformation, it becomes a solution to answer existing problems. This research aims to examine the implementation of the e-open application by the Bekasi City Population and Civil Registration Office as part of the government's efforts to improve public services through e-government innovation. Through a qualitative descriptive research method, the subjects used as informants were e-open application users and e-open operators with the sources in this research being the head of the Bekasi City administration information technology section, the head of the Bekasi City data presentation and processing section, and the community using the e-open application. Data collection was carried out using a purposive sampling technique which was carried out through in-depth interviews, observation, and documentation. The data analysis process uses phenomenological data analysis. The results of the research show that this application has significantly improved public services, ongoing support, and improvements in accessibility for optimal impact. So, this digital service innovation is a solution to transform public administration. This research concludes that e-open has succeeded in improving the provision of public services attracting the public, and bringing significant progress in public services, so this research has implications for the utilization of sustainable digital transformation in public services and is expected to be utilized in all government sectors.